Reconstitution of human peroxisomal β-oxidation in yeast - Knoblach, Barbara (FEMS Yeast Res, 2018)
We report the permanent introduction of the human peroxisomal β-oxidation enzymatic machinery required for straight chain degradation of fatty acids into the yeast, Saccharomyces cerevisiae. Peroxisomal β-oxidation encompasses four sequential reactions that are confined to three enzymes. The genes encoding human acyl-CoA oxidase 1, peroxisomal multifunctional enzyme type 2 and 3-ketoacyl-CoA thiolase were introduced into the genomic loci of their yeast gene equivalents. The human β-oxidation genes were individually tagged with sequence coding for GFP and expression of the protein chimeras as well as their targeting to peroxisomes was confirmed. Functional complementation of the β-oxidation pathway was assessed by growth on media containing fatty acids of different chain lengths. Yeast cells exhibited distinctive substrate specificities depending on whether they expressed the human or their endogenous β-oxidation machinery. The genetic engineering of yeast to contain a ‘humanized’ organelle is a first step for the in vivo study of human peroxisome disorders in a model organism.